Ergonomic Study of Work Posture Using the RULA Method in the Yellow Tofu Production Process at Pabuaran Village SMEs - Dwi Suryanto; Khairunnisa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
A study was conducted on “Analysis of Work Posture in Yellow Tofu Production Using the RULA Method to Reduce Complaints in Yellow Tofu SMEs in Gunung Sindur District, Pabuaran Village”. This was done because of the high number of complaints experienced by workers in the basic boiling section, as many as 13 (thirteen) complaints. The high number of complaints in the basic boiling process was known by using a standard Nordic questionnaire filled out by workers in the SME. The method used by the researcher was the Rapid Upper Limb Assessment (RULA) to determine whether the work posture used was at a high risk level or not. The analysis was carried out directly on workers in the basic boiling process using one sample of workers with three work activities, namely when pouring soybean juice, when taking boiled soybean juice, and when pouring boiled soybean juice. After analyzing the work posture using the Rapid Upper Limb Assessment (RULA) method, the three activities had a final score of 7 (seven) which means the risk level is high and the action must be to change the work posture immediately. This is due to the work posture involving a lowered neck, a bent torso, excessively raised arms and shoulders, the use of one foot support, and the lifting of excessively heavy loads when pouring soybean juice. Therefore, the next step that needs to be taken is to immediately change this posture to one with an upright neck, an upright torso, hands and shoulders not raised, the use of two foot supports, and a reduced load, to reduce complaints and prevent injury to workers in the bottom boiling section.